2013
DOI: 10.1111/nph.12396
|View full text |Cite
|
Sign up to set email alerts
|

Plant Defensin type 1 (PDF1): protein promiscuity and expression variation within the Arabidopsis genus shed light on zinc tolerance acquisition in Arabidopsis halleri

Abstract: SummaryPlant defensins are recognized for their antifungal properties. However, a few type 1 defensins (PDF1s) were identified for their cellular zinc (Zn) tolerance properties after a study of the metal extremophile Arabidopsis halleri. In order to investigate whether different paralogues would display specialized functions, the A. halleri PDF1 family was characterized at the functional and genomic levels.Eleven PDF1s were isolated from A. halleri. Their ability to provide Zn tolerance in yeast cells, their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 105 publications
(170 reference statements)
1
57
0
Order By: Relevance
“…These peptides are small highly stable cysteine-rich antimicrobial peptides, which are present in various multicellular organisms, including fungi, plants and animals. Defensins and defensin-like peptides are recognized as involved in the host's defense against bacteria [88], fungi [57,87] and viruses [19,56,112] and also acting in the plant's tolerance response to abiotic stresses [46,66,92].…”
Section: Introductionmentioning
confidence: 99%
“…These peptides are small highly stable cysteine-rich antimicrobial peptides, which are present in various multicellular organisms, including fungi, plants and animals. Defensins and defensin-like peptides are recognized as involved in the host's defense against bacteria [88], fungi [57,87] and viruses [19,56,112] and also acting in the plant's tolerance response to abiotic stresses [46,66,92].…”
Section: Introductionmentioning
confidence: 99%
“…Recent characterizations of each PDF1 of the multigenic family showed that, in the Arabidopsis genus, PDF1 proteins are mostly promiscuous in their zinc tolerance and antifungal roles, i.e., the same molecule can convey zinc tolerance to yeast ( Saccharomyces cerevisiae ) while inhibiting in vitro fungal pathogen growth ( Fusarium oxysporum f. sp. melonii ) (Marques et al, 2009; Shahzad et al, 2013). Overall, these datasets indicate that PDF1 s have a pivotal role in the plant response to both biotic (response to pathogens) and abiotic stress (here zinc excess).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of water deficiency on changes in the expression of genes encoding defensins is shown in Glycine max [22,36]. Cold also affects the expression of defensin genes [20,21]. Winter wheat has Tad1 gene, the expression of which is induced specifically under cold stress [21].…”
mentioning
confidence: 99%
“…There is both constitutive and inducible expression of genes, encoding plant defensins [11,14]. The main function of defensins is to inhibit fungal disease [8,11,15], but for some peptides there are antibacterial activity [16,17], inhibition of trypsin [18], and participation in the formation of resistance to heavy metals [19], cold stress [20,21], drought [22], salinity [23,24] and in developmental processes [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation